Think “HER2” different: integrative diagnostic approaches for HER2-low breast cancer - Marchiò, Caterina; Criscitiello, Carmen; Scatena, Cristian; Santinelli, Alfredo; Graziano, Paolo; Malapelle, Umberto; Cursano, Giulia; Venetis, Konstantinos; Fanelli, Giuseppe Nicolò; Pepe, Francesco; Berrino, Enrico; De Angelis, Carmine; et al. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2023)
This work explores the complex field of HER2 testing in the HER2-low breast cancer era, with a focus on methodological aspects. We aim to propose clear positions to scientific societies, institutions, pathologists, and oncologists to guide and shape the appropriate diagnostic strategies for HER2-low breast cancer. The fundamental question at hand is whether the necessary tools to effectively translate our knowledge about HER2 into practical diagnostic schemes for the lower spectrum of expression are available. Our investigation is centered on the significance of distinguishing between an immunohistochemistry (IHC) score 0 and score 1+ in light of the clinical implications now apparent, as patients with HER2-low breast cancer become eligible for trastuzumab-deruxtecan treatment. Furthermore, we discuss the definition of HER2-low beyond its conventional boundaries and assess the reliability of established diagnostic procedures designed at a time when therapeutic perspectives were non-existent for these cases. In this regard, we examine potential complementary technologies, such as gene expression analysis and liquid biopsy. Ultimately, we consider the potential role of artificial intelligence (AI) in the field of digital pathology and its integration into HER2 testing, with a particular emphasis on its application in the context of HER2-low breast cancer.